2018
DOI: 10.1177/1420326x17751594
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect of humidity on human comfort in a hot summer/cold winter zone in China

Abstract: Adaptation to different seasonal climates may affect human subjective responses to humidity. In this study, thermal comfort, humidity comfort and perceived air quality were investigated with subjects exposed in a climate chamber during spring, summer and winter. Sixty subjects were recruited in total, divided into groups of 20 subjects for each season. Temperature was set at three levels (cool, moderate and warm) during experiments in ranges of 20–28°C, 23–32°C, 16–28°C for spring, summer and winter, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
(43 reference statements)
2
13
0
2
Order By: Relevance
“…Berglund [52] experimentally demonstrated that for a sedentary person, a 30% increase in relative humidity had the same effect on the thermal balance and thermal sensation as a 1 o C increase in temperature. This is in agreement with Li et al [34], where the RH had a positive effect under cold temperatures. In his study, subjects who were on dried experimental clothes voted their thermal sensations from -2.2 to -1.3 (p < 0.05) when the RH was increased from 15% to 85% at steady state at 16 o C. Moreover, the subjects' TSV exhibited a strong linear relation with the SET.…”
Section: Negative Role Of Clothing Moisture In Cold Environmentssupporting
confidence: 94%
See 3 more Smart Citations
“…Berglund [52] experimentally demonstrated that for a sedentary person, a 30% increase in relative humidity had the same effect on the thermal balance and thermal sensation as a 1 o C increase in temperature. This is in agreement with Li et al [34], where the RH had a positive effect under cold temperatures. In his study, subjects who were on dried experimental clothes voted their thermal sensations from -2.2 to -1.3 (p < 0.05) when the RH was increased from 15% to 85% at steady state at 16 o C. Moreover, the subjects' TSV exhibited a strong linear relation with the SET.…”
Section: Negative Role Of Clothing Moisture In Cold Environmentssupporting
confidence: 94%
“…Subjects' sensation to air humidity was referred to the evaluation of wettedness sensation [44,45], but with a slightly fine-tuned description and scale. That is, the study defined the humidity sensation and adopted the seven-point bipolar scale instead of the seven-point unipolar scale (-3: very dry, -2: dry, -1: slightly dry, 0: neutral, +1: slightly humid, +2: humid, +3: very humid), which is consistent with [34]. In addition, subjects reported their thermal/humidity acceptability on a split scale with a gap in the middle, from clearly unacceptable (-1) to slightly unacceptable (-0.1), and thereafter from slightly acceptable (+0.1) to clearly acceptable (+1).…”
Section: Instruments and Measurementssupporting
confidence: 57%
See 2 more Smart Citations
“…the relative humidity in Chongqing, which is located in a hot summer and cold winter (HSCW) climate zone, often experiences > 70% RH [4][5][6][7]. Thus, people who visit…”
Section: Accepted Manuscriptmentioning
confidence: 99%